2020
DOI: 10.3389/fgene.2020.00891
|View full text |Cite
|
Sign up to set email alerts
|

Structural Variations Affecting Genes and Transposable Elements of Chromosome 3B in Wheats

Abstract: Structural variations (SVs) such as copy number and presence–absence variations are polymorphisms that are known to impact genome composition at the species level and are associated with phenotypic variations. In the absence of a reference genome sequence, their study has long been hampered in wheat. The recent production of new wheat genomic resources has led to a paradigm shift, making possible to investigate the extent of SVs among cultivated and wild accessions. We assessed SVs affecting genes and transpos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 61 publications
2
28
0
Order By: Relevance
“…In order to mitigate this problem, the interval that harbored a gene to be mapped was first identified using Insertion Site‐Based Polymorphisms (ISBP) markers, which mark junctions between neighboring TEs that are present in both the IWGSC RefSeq v1.0 and IWGSC RefSeq v2.1 assemblies. ISBPs are 150‐mers representing a unique sequence shaped by the junction of a TE and its insertion site (De Oliveira et al, 2020 ; Paux et al, 2010 ; Rimbert et al, 2018 ). Because ISBPs can be derived at each TE extremity, they are extremely abundant and well adapted for identifying corresponding loci across different assembly versions.…”
Section: Resultsmentioning
confidence: 99%
“…In order to mitigate this problem, the interval that harbored a gene to be mapped was first identified using Insertion Site‐Based Polymorphisms (ISBP) markers, which mark junctions between neighboring TEs that are present in both the IWGSC RefSeq v1.0 and IWGSC RefSeq v2.1 assemblies. ISBPs are 150‐mers representing a unique sequence shaped by the junction of a TE and its insertion site (De Oliveira et al, 2020 ; Paux et al, 2010 ; Rimbert et al, 2018 ). Because ISBPs can be derived at each TE extremity, they are extremely abundant and well adapted for identifying corresponding loci across different assembly versions.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies revealed a partitioning of the wheat genome based on different structural and functional features, including the recombination rate, gene and transposable element (TE) densities, gene expression breadth, histone modifications, as well as gene and TE structural variation rate (Choulet et al., 2014; De Oliveira et al., 2020; IWGSC, 2018; Pingault et al., 2015). Consequently, chromosomes can be divided into five chromosomal compartments: the short arm distal R1, the short arm proximal R2a, the centromeric‐pericentromeric C, the long arm proximal R2b and the long arm distal R3 regions.…”
Section: Resultsmentioning
confidence: 99%
“…This differential association with active or repressive histones marks have already been reported in other species, such as potato where CNV frequency increased in genes lacking histone marks associated with permissive transcription (Hardigan et al., 2016). In wheat, we showed recently that genes affected by intra‐ and interspecific copy number variations were enriched in H3K27m3 (De Oliveira et al., 2020).…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations